Combined gene deletion of dihydrofolate reductase-thymidylate synthase and pteridine reductase in Leishmania infantum - Bhattacharya, Arijit; Leprohon, Philippe; Ouellette, Marc (PLOS Neglected Tropical Diseases, 2021)
Author summary The protozoan parasite Leishmania is auxotroph for folate and unconjugated pterins and salvages both from the mammalian host. Two enzymes of the folate metabolism pathway, namely the bifunctional dihydrofolate reductase-thymidylate synthase (DHFR-TS) and the pteridine reductase 1 (PTR1), are being evaluated for drug discovery and repurposing of existing anti-metabolites. Despite their apparent potential, development of DHFR-TS and PTR1 targeted chemotherapy against Leishmania is still awaiting. Here we revisited folate metabolism at the genomic level and report on the identification of known resistance genes alongside some new ones. Through gene disruption studies we found that L. infantum DHFR-TS null mutants are thymidine auxotroph and that these can be rescued by the bacterial flavin dependent thymidylate synthase ThyX. We also found that PTR1 is essential in the absence of a functional DHFR-TS even in the presence of ThyX or thymidine supplementation, indicating the essential role of reduced pterins or folate beyond thymidine synthesis. This study indicates that simultaneous targeting of DHFR-TS and PTR1 will be required for the development of anti-folate chemotherapy against Leishmania.